Implementasi Pembelajaran Diferensiasi dalam Mengatasi Keberagamaan Gaya Belajar Siswa di Sekolah Dasar - Ita Puspitasari; Putri Hasanah Kusumaningrum; Septiana Ardiningsih; Sulisetias Dinarti; Teni Wahyuningsih (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Differentiated learning is learning that pays attention to, provides and recognizes student diversity in learning according to students' motivation, interests and learning preferences. The diversity of student learning styles requires selecting appropriate teaching strategies so that students' learning style strengths can develop optimally. This research uses a literature review method with the technique of collecting important information by reading, recording and managing research materials. This research aims to systematically review the literature to find the implementation of differentiated learning in addressing the diversity of student learning styles. Through this research, teachers are expected to be able to facilitate the diversity of students' learning styles by implementing differentiated learning.